Isolation and study of the basic properties of Pseudomonas syringae bacteriophages - Bekkaliyeva A.K.; Bogdanov I.I. (Ветеринария и кормление)
In industry and agriculture, interest in bacteriophages is due to their use to control bacterial populations that are harmful in production and affect agricultural plants. The use of various biological products to control such bacteria is one of the promising methods of biological protection of plants from infectious diseases. This article is devoted to research on the isolation and study of the basic biological properties of bacteriophages Pseudomonas syringae.124 samples were used to isolate bacteriophages from environmental objects (wastewater, soil from various sites) and reference bacteria strains Pseudomonas syringae № 3 (obtained from the collection of the Museum of the Department of MVEiVSE of the Ulyanovsk GAU) and strain B-10917 were used as indicator strain. (obtained from the collection of the BRC VKPM SIC "Kurchatov Institute" - GosNIIgenetika). The presence of phage was determined by the Otto method. As a result of the study, 8 bacteriophages were isolated. PFU of bacteriophages Pseudomonas syringae are round forms with clear transparent centers without secondary growth with a diameter of 0.5 to 5.0 mm. The results of studying the following biological properties of the isolated bacteriophages are also given: lytic activity according to Appelman and Grazia, specificity of the bacteriophage, the optimal ratio of bacteriophage and culture is selected. Appelman's lytic activity ranged from 10-4 to 10-8; Grace from 1.0 ± 0.1ґ106 to 2.0 ± 0.1ґ109 (PFU / ml). The spectrum of lytic activity of phages ranged from 42.9% to 71.4%. All bacteriophages had strict specificity. The results of this study can be used to develop a biological product based on bacteriophages that can be used as an effective method for the indication and identification of bacteria Pseudomonas syringae in objects of sanitary surveillance, as well as a means to protect plants from bacterial diseases.